An Analysis on English Teacher Strategies in Teaching Reading Comprehension - Yulia Ade Saputri; Syamsul Rizal; Zelvia Liska Afriani (Jadila: Journal of Development and Innovation in Language and Literature Education, 2021)
The purpose of this study was to analyze what strategies the teacher used in teaching reading comprehension and how the teacher applies the strategies used in teaching reading comprehension. The subjects of this study were teacher who taught English at SMAN 10 Kota Bengkulu . This type of research is designed as descriptive qualitative research. To collect data in the study,  researcher used Checklist Observation, Interview as an instrument in collected data and documentation. The procedure of this research is by means of researchers coming and participating in seeing and understanding how the teacher teaches reading comprehension in the classroom. The results of the study found that the two strategies used by the teacher, Scaffolding and QARs (Question Answers Relationship). Scaffolding strategy students can develop ideas that can be read by students and make students confident in reading comprehension. QARs (Question Answer Relationship), the teacher is able to know the extent to which students understand what the teacher has given them and the limits of the students' ability to do assignments after reading the text that has been given. Thus, it can be concluded that the teacher is good enough to implement this strategy in the classroom, but was slightly hindered by its application during the Covid-19 Pandemic.